FORESEEING STOCK PRICE– A DETAILED SURVEY AND MODELLING - R. Suganya, Dr. A. Sasi Kumar (International Journal of Advanced Science and Technology, 2020)
Stock exchange expectation is a specialty of anticipating the future estimation of specific financial script depend on the analysis of the past data. Stock market forecast is significant as it includes greater speculation and returns in the field of scholastic and budgetary research. Despite the fact that it is profoundly unpredictable there are procedures accessible to foresee its future worth. It is extraordinary advantageous to use AI strategy to anticipate the estimation of the stock cost. Fuzzy rationale, Neural system and hereditary calculation are recognized to be the main AI method in stock value forecast. It follows delicate procedures. As it gives high scope of precision and speed, utilization of delicate processing procedures are energetically prescribed. The thought behind the expectation is to utilize less number of sources of info information and to accomplish the best outcome. This paper reviews in excess of 15 related articles that are publised under the subject stock value forecast. The choice of the papers depend on the different models in delicate processing that are used to accomplish the stock cost.In the later part,we also proposed a novel model to predict the future stock price. Keywords: Fuzzy rule, Genetic Approach, Neural Networks, Stock Prediction, Time Series.